Development of immuno- nanoparticles for targeting schistosoma parasites - Abdul-Ghany, Eman Rabie (AUC Knowledge Fountain, 2017)
Praziquantel (PZQ) is the drug of choice for treatment of schistosomiasis since its discovery in 1972. According to World Health Organization (WHO), schistosomiasis is the second most prevalent parasitic disease worldwide that has no effective vaccine yet. Schistosoma parasites infect more than 200 million people in about 76 countries and about 700 million people are at risk.PZQ is not only used for treatment of schistosomiasis, but it is also used for control of other parasitic diseases and it is included on the Model List of Essential Medicines of WHO. Parasitic diseases, despite their significant global burden, have been rather under researched by drug discovery companies as compared to other diseases mainly due to complexities of parasitic infections and lack of economic motivations. In such scenario, nanomedicine has a crucial role to play in improvement of the current anti-parasitic agents by their delivering in a targeted manner to the schistosome parasites in host blood circulation. Hence, selective drug delivery is an important approach with great potential for overcoming problems associated with the systemic toxicity and poor bioavailability of PZQ. This study aims at overcoming the inherent drawbacks of PZQ through formulation, optimization and evaluation of PZQ-loaded biodegradable PLGA “Poly (D,L lactide-coglycolide)” nanoparticles (NPs) that were surface conjugated with polyclonal antibodies (pAb) specific for schistosome surface antigens (sAg) for active targeting and treatment of schistosomiasis. PZQ was encapsulated in biodegradable PLGA NPs using single emulsion-solvent evaporation method. Various parameters were investigated and optimized like drug: polymer ratio, surfactant concentration and osmotic effect of adding salts to the external aqueous phase. PZQ-loaded NPs were characterized for drug content and drug release rate using HPLC, particlesize, particle size distribution and ζ-potential using dynamic light scattering, surface morphology using scanning electron microscopy (SEM) and atomic force microscopy (AFM), and drug physical and chemical integrity using differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR) spectroscopy. Spherical PLGA NPs with smooth and discrete surface were prepared. The physicochemical properties of the prepared NPs were investigated and the optimum formulation was selected. The selected formulation was monodispersed NPs 200.8±4.02nm in diameter and negatively charged surface (-21.03±3.08mV). PZQ- loaded PLGA NPs showed sustained release profile from the optimum formulation with the highest encapsulation efficiency and drug loading (94.19±3.46% and 47.09±3.46% respectively). Specific anti- schistosomal pAb specific against schistosome sAg was prepared, purified and characterized. Surface functionalization of the optimized PZQ-loaded PLGA NPs with antischistosomal pAb was then achieved using both physical adsorption and chemical conjugation methods using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and Nhydroxysuccinimide (NHS) mediated cross linking agents. The pAb- conjugated immuno-NPs showed higher coupling efficiency than the pAb- adsorbed NPs (89.31±1.78 and 64.2±2.87%, respectively). Re-evaluation of the physical properties of NPs and the reactivity of pAb after coupling reactions was performed. The immuno-NPs indicated optimum properties with preserved bioactivity of the attached antibodies. Thus, it was concluded that pAb-conjugated PLGA NPs provide an efficient and targeted delivery of PZQ, presenting a potential preliminary delivery system for treatment of Schistosomiasis in near future.